The Elasticity of the Migrant Labor Supply: Evidence from Temporary Filipino Migrants - Simone Bertoli; Jesús Fernández-Huertas Moraga; Sekou Keita (Institute for the Study of Labor (IZA), 2016)
The effect of immigration on host and origin countries is mediated by the way migrants take their labor supply decisions. We propose a simple way of integrating the traditional random utility maximization model used to analyze location decisions with a classical labor demand function at destination. Our setup allows us to estimate a general upper bound on the elasticity of the migrant labor supply that we take to the data using the evolution of the numbers and wages of temporary overseas Filipino workers between 1992 and 2009 to different destinations. We find that the migrant labor supply elasticity can be very large. Temporary migrants are very reactive to economic conditions in their potential destinations.
Keywords: F22; J31; J38; J61; O15; 330; labor supply elasticity; temporary migration; international migration; multilateral resistance to migration